Salman Mosque as a Center of Islamic Da'wah and Spiritual Laboratory for Campus Community - Yedi Purwanto; Ahmad Sarbini; Jundi Abdullah; Angga Qadafi (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2019)
This research explains the role of the Salman mosque of ITB (Institut Teknologi Bandung) as the center of Islamic da'wah and the spiritual laboratory for the campus community in preaching Islamic teachings as rahmatan lil’alamin (mercy to the world). This research explicitly reveals the role of the Salman mosque in the development of Islamic da'wah for students, educating moderate character for students, and the concept of Salman mosque as a spiritual laboratory for the campus community. The research methods was descriptive and the data were obtained through the response of mosque members and they were analyzed qualitatively. The findings showed that the Salman mosque acts as a Madani mosque with complete facilities, namely, educational facilities, open green spaces, da’wah institutions, and economic development institutions for the Muslim community. Therefore, the Salman mosque becomes a pleasant place for families, play and learning spaces for children, and center for spiritual studies, as well as center of civilization in the development of science, technology, arts and culture.Tulisan ini menjelaskan peran masjid Salman ITB (Institut Teknologi Bandung) sebagai pusat dakwah Islamiyah dan laboratorium ruhani masyarakat kampus dalam mendakwahkan ajaran Islam yang rahmatan lil’alamin. Secara khusus penelitian ini mengungkapkan peran masjid Salman ITB dalam pengembangan dakwah Islamiyah bagi mahasiswa, pendidikan karakter moderat bagi mahasiswa dan konsep masjid sebagai laboratorium ruhani bagi masyarakat kampus. Penelitian menggunakan metode deskriptif dengan pendekatan kualitatif yang dilengkapi respons jamaah ini menemukan bahwa masjid Salman ITB berperan sebagai masjid madani dengan fasilitas lengkap, yaitu sarana pendidikan, ruang hijau terbuka, lembaga dakwah, dan lembaga pengembangan ekonomi umat. Oleh karena itu, masjid Salman ITB menjadi tempat menyenangkan bagi keluarga, ruang bermain dan belajar bagi anak-anak, serta pusat studi kajian ruhani dan pusat peradaban dalam pengembangan sains, teknologi, seni dan budaya.